2015
DOI: 10.1002/adma.201503013
|View full text |Cite
|
Sign up to set email alerts
|

The Interplay of Quantum Confinement and Hydrogenation in Amorphous Silicon Quantum Dots

Abstract: Hydrogenation in amorphous silicon quantum dots (QDs) has a dramatic impact on the corresponding optical properties and band energy structure, leading to a quantum‐confined composite material with unique characteristics. The synthesis of a‐Si:H QDs is demonstrated with an atmospheric‐pressure plasma process, which allows for accurate control of a highly chemically reactive non‐equilibrium environment with temperatures well below the crystallization temperature of Si QDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 39 publications
0
25
0
Order By: Relevance
“…17 Hence, it is important to develop alternative QDs with good optical and electrical properties but composed of materials with low toxicities. This has driven development of heavy metal free alternatives including group IV materials [18][19][20][21][22][23] (e.g. Si, Ge, C) and ternary I-III-VI alloys 24 (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…17 Hence, it is important to develop alternative QDs with good optical and electrical properties but composed of materials with low toxicities. This has driven development of heavy metal free alternatives including group IV materials [18][19][20][21][22][23] (e.g. Si, Ge, C) and ternary I-III-VI alloys 24 (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, nanoscale materials and in particular QDs tend to exhibit highly pure “inner cores” due to thermodynamic stability, so that if defects are present these tend to remain at the surface. This was, for instance, observed in the synthesis of Si QDs, whereby the introduction of even very small amount of hydrogen in the core (not at the surface) can determine the amorphous versus crystalline nature of the QD . Secondly, defects at the surface are easier to address with a range of surface treatments, which can achieve superior passivation and eliminating most defects and dangling bonds .…”
Section: Third Generation Photovoltaics (Pvs)mentioning
confidence: 98%
“…This was, for instance, observed in the synthesis of Si QDs, whereby the introduction of even very small amount of hydrogen in the core (not at the surface) can determine the amorphous versus crystalline nature of the QD. [15] Secondly, defects at the surface are easier to address with a range of surface treatments, which can achieve superior passivation and eliminating most defects and dangling bonds. [16][17][18] There are also aspects that relate to the device architecture and in particular it should be noted that mobility requirements, e.g., first generation PVs are far higher than those for 3-Gen devices, due to the absorber layer expected to be order of magnitudes thinner in the latter ones.…”
Section: Third Generation Photovoltaics (Pvs)mentioning
confidence: 99%
“…Si NPs with high crystallinity and distinctive shapes can be synthesized without H 2 addition to the Ar and SiH 4 gas mixture when RF microplasmas are used. Moreover, the PL emissions of the Si NPs can be tuned in the visible range by adjusting the H 2 concentration . Recently, it has been reported that Si NPs can also be synthesized by microplasma‐assisted liquid‐phase processing at ambient conditions .…”
Section: Production Of Advanced Nanomaterialsmentioning
confidence: 99%